The influence of the characteristics of breaking test units on the results of testing plastic properties of the wire RML - N. A. Akunets (Литьë и металлургия)
For metal products manufactured by hardware shops (metal cord, PML wire and side bronzed wire), the most important mechanical properties are those, that determine the strength, ductility and other characteristics of the materials. The article describes the characteristics of breaking test unit that affect the results of tests of plastic properties of RML wire. The analysis of the test conditions and factors affecting the test results was made.